Baicalin suppresses NLRP3 inflammasome and nuclear factor-kappa B (NF-κB) signaling during Haemophilus parasuis infection. (December 2016) - Fu, Shulin; Xu, Lei; Li, Sali; Qiu, Yinsheng; Liu, Yu; Wu, Zhongyuan; Ye, Chun; Hou, Yongqing; Hu, Chien-An Andy
Abstract Haemophilus parasuis (H. parasuis ) is the causative agent of Glässer's disease, a severe membrane inflammation disorder. Previously we showed that Baicalin (BA) possesses anti-inflammatory effects via the NLRP3 inflammatory pathway in an LPS-challenged piglet model. However, whether BA has anti-inflammatory effects uponH. parasuis infection is still unclear. This study investigated the anti-inflammatory effects and mechanisms of BA onH. parasuis -induced inflammatory responses via the NF-κB and NLRP3 inflammasome pathway in piglet mononuclear phagocytes (PMNP). Our data demonstrate that PMNP, when infected withH. parasuis, induced ROS (reactive oxygen species) production, promoted apoptosis, and initiated transcription expression of IL-6, IL-8, IL-10, PGE2, COX-2 and TNF-α via the NF-κB signaling pathway, and IL-1β and IL-18 via the NLRP3 inflammasome signaling pathway. Moreover, when BA was administrated, we observed a reduction in ROS production, suppression of apoptosis, and inhibition of the activation of NF-κB and NLRP3 inflammasome signaling pathway in PMNP treated withH. parasuis . To our best knowledge, this is the first example that uses piglet primary immune cells for anH. parasuis infection study. Our data strongly suggest that BA can reverse the inflammatory effect initiated byH. parasuis and possesses significant immunosuppression activity, which represents a promising therapeutic agent in the treatment ofH. parasuis infection.